Synergistic effects of Lecanicillium lecanii and botanical extracts on growth and virulence against Nilaparvata lugens Stål. (Hemiptera: Delphacidae) - Lutfi Afifah; Mela Rizki Fauziyyah; Nurcahyo W. Saputro; Fawzy M. Bayfurqon; Anik Kurniati (Universitas Lampung, 2026)
This study evaluated the synergistic potential of the entomopathogenic fungus Lecanicillium lecanii combined with plant extracts from Dioscorea hispida and Annona muricata (soursop) for controlling the brown planthopper (Nilaparvata lugens). The research addresses the limited adoption of integrated pest management (IPM) and the continued reliance on chemical pesticides, which contribute to environmental risks and pest resistance. The experiment was conducted in two stages. The first stage examined fungal growth on media supplemented with different concentrations of plant extracts. The addition of plant extracts significantly enhanced colony growth, conidial density, and germination compared with the control. The highest conidial density (1.38 × 10⁹ conidia/mL) and germination rate (91.75%) were obtained with D. hispida extract at 5 g/L, indicating superior nutritional support for fungal development. The second stage evaluated the virulence of the optimized fungal culture against N. lugens nymphs. Mortality increased in both dose-dependent and time-dependent patterns. The highest concentration (10⁹ conidia/mL) resulted in 92.71% mortality within seven days, with a lethal time (LT₅₀) of 3.27 days. Improved conidial density and germination contributed directly to enhanced fungal infectivity and pathogenicity. In conclusion, supplementation of L. lecanii with D. hispida and A. muricata extracts improves fungal growth and significantly increases its effectiveness against N. lugens. This synergistic approach provides a promising environmentally friendly alternative to chemical insecticides and supports the development of sustainable IPM strategies for tropical rice agroecosystems.